O emergir de um novo território camponês: conquistas e transformações nos domínios do latifúndio o caso de São Gabriel - RS - Santos, Anderson Luiz Machado dos (2012)
On the threshold of XXI century the agrarian issue (re)means itself in the paradoxical movement in space and time in which is inserted. One of the revelatory processes of this movement relates to the creation and recreation of the peasantry. Within the rural areas of Brazil, the popular social movements, such as the Movement of Landless Workers (MLW), play an elemental role for this creation and recreation. This process is marked by conflicts, since the struggle for land, until the fight to live and reproduce in the conquered land. Thus, the agrarian issue it is limited in a field of conflicts, where it develops a territory dispute between different actors: the peasants, landowners, agribusiness representatives and the state apparatus. In Rio Grande do Sul, region of Campanha Gaúcha, traditionally identified with the secular area of latifundia rancher, recently converted into space for the expansion of agribusiness, it is found a locus of this dispute. One of the space-time where this process has become emblematic is the municipality of São Gabriel. In this space-time, in their struggle to spatialize and territorialize themselves, the MLW obtained achievements such as the formation of rural settlements; on the other hand, the subjects who experienced the struggle for land constantly suffer different forms of violence. This research aims to understand the main changes produced in rural areas of São Gabriel, from the struggle for land and in the land experienced by the families organized by the MLW. The analysis of the issue is conducted from the perspective where the geographic space is considered in its historicity and totality, in movement of relations. Seeking to develop a qualitative research are articulated two research plans: the theoretical and the empirical, through which goes from the empirical intuitive to the theoretical abstraction and vice versa, to approach successively of the object of analysis and refunding it as synthesis of multiple dimensions. From these methodological procedures could be understood how, in consequence of social processes as the new relationship that the families have establish with the land in the conquered settlements, the labor relations, the political culture of the organization and participation, as well as different strategies designed to the development of settlements, are modified the forms, the functions and the structure of the geographic space. Also, these individuals develop an active territoriality that contributes to the transformation of the power relations and the local political culture. Insofar as they reterritorialize themselves in the space, the individuals reinvent their way of life and begin to share a subordinate class position in the web of the power relations inherent to the territorial dispute. When faced with the dilemma of subalternity, they prepare their answers and their different plans for the future, in a movement of material and symbolic appropriation of the conquered space, which results in the construction of a new territory, the territory of the peasant-settlers.